Sexually Dimorphic Formation of the Preoptic Area and the Bed Nucleus of the Stria Terminalis by Neuroestrogens - Tsukahara, Shinji; Morishita, Masahiro (Frontiers in Neuroscience, 2020)
Testicular androgens during the perinatal period play an important role in the sexual differentiation of the brain of rodents. Testicular androgens transported into the brain act via androgen receptors or are the substrate of aromatase, which synthesizes neuroestrogens that act via estrogen receptors. The latter that occurs in the perinatal period significantly contributes to the sexual differentiation of the brain. The preoptic area (POA) and the bed nucleus of the stria terminalis (BNST) are sexually dimorphic brain regions that are involved in the regulation of sex-specific social behaviors and the reproductive neuroendocrine system. Here, we discuss how neuroestrogens of testicular origin act in the perinatal period to organize the sexually dimorphic structures of the POA and BNST. Accumulating data from rodent studies suggest that neuroestrogens induce the sex differences in glial and immune cells, which play an important role in the sexually dimorphic formation of the dendritic synapse patterning in the POA, and induce the sex differences in the cell number of specific neuronal cell groups in the POA and BNST, which may be established by controlling the number of cells dying by apoptosis or the phenotypic organization of living cells. Testicular androgens in the peripubertal period also contribute to the sexual differentiation of the POA and BNST, and thus their aromatization to estrogens may be unnecessary. Additionally, we discuss the notion that testicular androgens that do not aromatize to estrogens can also induce significant effects on the sexually dimorphic formation of the POA and BNST.